Deictic and Propositional Meaning—New Perspectives on Language in Schizophrenia - Zimmerer, Vitor C.; Watson, Stuart; Turkington, Douglas; Ferrier, I. Nicol; Hinzen, Wolfram (Frontiers in Psychiatry, 2017)
Emerging linguistic evidence points at disordered language behavior as a defining characteristic of schizophrenia. In this article we review this literature and demonstrate how a framework focusing on two core functions of language - reference and propositional meaning - can conceptualize schizophrenic symptoms, identify important variables for risk assessment, diagnosis and treatment, and inform cognitive behavioral therapy and other remedial approaches. We introduce the linguistic phenomena of deictic anchoring and propositional complexity, explain how they relate to schizophrenic symptoms, and demonstrate how they can be tracked in language behavior.